Factors Influencing Indonesian Internet Users Intention on Buying Books Online - Beatrik Messah (The Winners, 2003)
The purpose of this research is to discover and analyse factors influencing Indonesian internet users intention on buying books online. Certain factors will be investigated are demographic, features, convenience, web design, and security. This research used questionaires to obtain data from the respondents. After the data collected, SPSS software is used to process the data with using Chi-Square test. The result found that features, convenience, and security factors of online bookstores and level of education, income, and occupation of the Indonesian Internet Users influence the people intention on buying books online. In the other hand, web design of the online bookstores and the age of the Indonesian internet users have no influence on their intention on buying books online.